Novel acid-labile subunit ( IGFALS ) mutation p.T145K (c.434C>A) in a patient with ALS deficiency, normal stature and immunological dysfunction - Schreiner, Felix (2013)
We report a novel missense mutation p.T145K in the insulin-like growth factor (IGF) acid-labile subunit (IGFALS) gene identified in a Turkish patient with normal growth, transient pancytopenic episodes and signs of immunological dysfunction. Because of recurrent cutaneous mycoses and absence of pubertal development until the age of 14.75 years we determined several endocrine parameters in order to rule out autoimmune-polyendocrine syndromes. Despite a normal height between the 25th and 50th percentile we found severely decreased IGF-1 and undetectably low IGFBP-3 levels. Laboratory signs of immunological dysfunction included reduced total lymphocyte count with diminished B and T helper cell fractions, decreased serum concentrations of IgM and IgG subclass 4, and elevated antinuclear antibody and anti-dsDNA titers as well as persistently high interleukin-2-receptor levels. Further endocrine work-up revealed elevated fasting insulin and undetectably low ALS serum levels, leading to the diagnosis of ALS deficiency. Sequencing of the coding region of the IGFALS gene showed a novel homozygous missense mutation (c.434C>A; p.T145K). Since immunological abnormalities have not been reported in more than 20 ALS-deficient patients so far and our patient was born to consanguineous parents, a second autosomal recessive defect is likely to underlie the immunological phenotype, although a causative role of IGFALS p.T145K cannot be entirely ruled out.